Contemporary penal trends. Modern or postmodern? - Lucken, Karol (The British journal of criminology, 1998)
The postmodern argument in the punishment literature is in its formative beginnings. The achievements in applying a postmodern framework to the study of punishment, thus far, have been speculative and empirically narrow. Consequently, a question that remains is do postmodern or modern conceptions capture the form and function of contemporary penality'? The current study addrerses this question by exploring contemporary penality as it exists for those working in the penal system. Three salient trends are identified penality as a balancing act, corporate penality, and offender subsidization of penality. A modern and pastmodern interpretation are considered in the analysis of these trends. it is concluded that contemporary penality is not qualitatively different from past penality, and therefore, is best understood in the context of modernity